Strategic change and termination of interfirm partnerships - Cui, Anna Shaojie; Calantone, Roger J.; Griffith, David A. (Strategic Management Journal, 2011)
Abstract An evolutionary perspective of the resource‐based view is adopted to understand how changes in a partner firm's overall strategy may influence the firm's interfirm partnerships over time. We contend that changes in a partner firm's overall resource deployment strategy and partnering strategy influence the value and uniqueness of partnership resources. These changes alter the competitive advantage associated with partnership resources, affecting the propensity of partnership termination. An event history analysis is employed with 150 joint ventures over the period 1990 to 2001 to examine partnership termination within a longitudinal dataset. With initial partnership conditions controlled for, the results indicate significant influences of various changes in partner firm overall resource deployment strategy and partnering strategy on the propensity of termination. Further, competitor imitative activities are found to increase the propensity of termination as they reduce the uniqueness of partnership resources. This study provides support for an evolutionary perspective of resource value and competitive advantage that incorporates strategic change over time. Copyright © 2010 John Wiley & Sons, Ltd.